AhR Ligands Modulate the Differentiation of Innate Lymphoid Cells and T Helper Cell Subsets That Control the Severity of a Pulmonary Fungal Infection - de Araújo, Eliseu F.; Loures, Flávio V.; Preite, Nycolas W.; Feriotti, Cláudia; Galdino, Nayane AL; Costa, Tânia A.; Calich, Vera L. G. (Frontiers in Immunology, 2021)
In agreement with other fungal infections, immunoprotection in pulmonary paracoccidioidomycosis (PCM) is mediated by Th1/Th17 cells whereas disease progression by prevalent Th2/Th9 immunity. Treg cells play a dual role, suppressing immunity but also controlling excessive tissue inflammation. Our recent studies have demonstrated that the enzyme indoleamine 2,3 dioxygenase (IDO) and the transcription factor aryl hydrocarbon receptor (AhR) play an important role in the immunoregulation of PCM. To further evaluate the immunomodulatory activity of AhR in this fungal infection, Paracoccidioides brasiliensis infected mice were treated with two different AhR agonists, L-Kynurenin (L-Kyn) or 6-formylindole [3,2-b] carbazole (FICZ), and one AhR specific antagonist (CH223191). The disease severity and immune response of treated and untreated mice were assessed 96 hours and 2 weeks after infection. Some similar effects on host response were shared by FICZ and L-Kyn, such as the reduced fungal loads, decreased numbers of CD11c+ lung myeloid cells expressing activation markers (IA, CD40, CD80, CD86), and early increased expression of IDO and AhR. In contrast, the AhR antagonist CH223191 induced increased fungal loads, increased number of pulmonary CD11c+ leukocytes expressing activation markers, and a reduction in AhR and IDO production. While FICZ treatment promoted large increases in ILC3, L-Kyn and CH223191 significantly reduced this cell population. Each of these AhR ligands induced a characteristic adaptive immunity. The large expansion of FICZ-induced myeloid, lymphoid, and plasmacytoid dendritic cells (DCs) led to the increased expansion of all CD4+ T cell subpopulations (Th1, Th2, Th17, Th22, and Treg), but with a clear predominance of Th17 and Th22 subsets. On the other hand, L-Kyn, that preferentially activated plasmacytoid DCs, reduced Th1/Th22 development but caused a robust expansion of Treg cells. The AhR antagonist CH223191 induced a preferential expansion of myeloid DCs, reduced the number of Th1, Th22, and Treg cells, but increased Th17 differentiation. In conclusion, the present study showed that the pathogen loads and the immune response in pulmonary PCM can be modulated by AhR ligands. However, further studies are needed to define the possible use of these compounds as adjuvant therapy for this fungal infection.